ECONOMIC EFFECTS OF THE CREDITORSʼ RIGHTS PROTECTION - Lekpek, Ahmedin (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
The readiness of creditors to satisfy the credit demand of the population and the economy under mutually acceptable conditions directly depends on the legal protection degree that creditors enjoy. In this paper, we deal with the protection of creditorsʼ rights and the instruments used for this purpose. The aim of this paper is to consider the economic effects that arise as a result of the application of instruments of the creditorsʼ rights protection, which affect both the financial position of creditors and debtors and the stability and efficiency of the financial and economic system as a whole. The research results show that the existence of an adequate level of protection of creditorsʼ rights has a strong positive impact on the size and activity of the credit market. On the other hand, the application of various instruments of the creditorsʼ rights protection can cause both positive and negative effects on the creditors position. Also, excessively high level of creditorsʼ protection can significantly worsen the position of debtors and, consequently, in the long run, the position of creditors themselves.
Keywords: creditors; protection of creditorsʼ rights; debtors; collateral; covenants; currency clause; credit insurance